Evaluation of waste management of health services generated in indigenous health care (Research, Society and Development, 2022)
The study aimed to evaluate the management of Health Service Waste (RSS) in Indigenous Lands in Maranhão. The study methodology consisted of monitoring, from January to December 2018, the indigenous health care and the procedures for managing the RSS generated in the villages of Maranhão. Initially, a segregation and classification of these wastes was carried out in accordance with ANVISA's RDC nº. 222/2018. Then, the RSS were quantified, by class, and the treatment, destination and final disposal that are given to them were identified. The results showed that most of the generated RSS fall into Group A, with a total amount of 1,314 kg. As for the treatment of waste classified in groups A1, B and E, all are sent for incineration. It is noteworthy that the destination and final disposal are correct when there are Basic Indigenous Health Units (UBSI) implanted in the villages. However, the RSS generated in villages that do not have these units, present the stage of limited and problematic segregation, which implies an environmentally compromised treatment and disposal. The elaboration and implementation of a separate Health Services Waste Management Plan (PGRSS) for the units and villages, and a specialized permanent education program for the multidisciplinary indigenous health teams (EMSIs) seems to be a viable alternative to improve the process of RSS management in these villages that do not have UBSI, but that receive health care in their huts.